Mesenchymal Stem Cells Therapy in critical COVID-19 patient: a case report - Novi Sukirto; Zainul Arifin; Barkah Purwanto; Auliya Azisah Mansur; Naila Sistharani; Sumardi Sumardi (Universitas Ahmad Dahlan, 2022)
COVID-19 pneumonia with critical symptoms causes acute respiratory distress syndrome (ARDS) and multiple organ dysfunction syndromes (MODS) which can be severe complications until death. One therapy for Covid-19 critical was to suppress the effects of cytokine storms, which was administered by Mesenchymal Stem Cells therapy. In this case, we will report a case of COVID-19 with a critical patient that was given MSC therapy there were good outcomes in this case which were improvement of the clinical symptoms and prevent death. ABSTRAK Pneumonia COVID-19 dengan gejala kritis menyebabkan sindrom gangguan pernapasan akut (ARDS) dan sindrom disfungsi organ multipel (MODS) yang dapat menjadi komplikasi berat hingga kematian. Salah satu terapi kritis Covid-19 adalah menekan efek badai sitokin, yang dilakukan dengan terapi Sel Punca Mesenkim. Dalam kasus ini, kami akan melaporkan kasus COVID-19 dengan pasien kritis yang diberikan terapi MSC ada hasil yang baik dalam kasus ini yaitu perbaikan gejala klinis dan mencegah kematian